Development of an Android-Based Educational Game with Gamification for Algorithms and Data Structures - Gita Damayanti; Miraekel Lebang Malik; Firdayani Syarifuddin; Ibnu Hajar Manippi; Eva Ulfiani; Era Fasira (Jurusan Teknik Informatika dan Komputer, 2024)
This study aims to develop and evaluate an Android-based educational game incorporating gamification elements for teaching Algorithms and Data Structures (ADS). ADS is recognized as a fundamental yet challenging subject in computer science education due to its abstract concepts and dynamic processes. Traditional lecture-based instruction often results in low engagement and limited conceptual understanding. Therefore, this study proposes a gamified mobile learning solution to enhance student motivation and learning outcomes. A Research and Development (R&D) approach using the ADDIE model was employed to design and develop the application, followed by a quasi-experimental non-equivalent control group pretest–posttest design to evaluate its effectiveness. Participants consisted of 74 undergraduate students divided into an experimental group (n = 38) using the Android-based gamified application and a control group (n = 36) receiving conventional instruction. Data were analyzed using paired and independent samples t-tests with a significance level of 0.05. Results indicated a significant difference in posttest scores (t = 6.64, p < 0.001), with the experimental group achieving a higher mean (M = 82.47) compared to the control group (M = 71.28). The effect size was large (Cohen’s d = 1.54). Motivation scores were also higher in the experimental group (M = 4.31), and usability evaluation yielded an excellent System Usability Scale (SUS) score of 81.45. The study is limited to a single institution and short intervention duration. This research contributes empirical evidence that gamified Android-based learning can significantly improve cognitive achievement and motivation in ADS courses.